Improvement of fibrin clot structure after factor VIII injection in haemophilia A patients treated on demand - Antovic, Aleksandra; Mikovic, Danijela; Elezovic, Ivo; Zabczyk, Michael; Hutenby, Kjell; Antovic, Jovan P. (Thrombosis and Haemostasis, 2014)
Patients with haemophilia A have seriously impaired thrombin generation due to an inherited deficiency of factor (F)VIII, making them form unstable fibrin clots that are unable to maintain haemostasis. Data on fibrin structure in haemophilia patients remain limited. Fibrin permeability, assessed by a flow measurement technique, was investigated in plasma from 20 patients with severe haemophilia A treated on demand, before and 30 minutes after FVIII injection. The results were correlated with concentrations of fibrinogen, FVIII and thrombin-activatable fibrinolysis inhibitor (TAFI), and global haemostatic markers: endogenous thrombin potential (ETP) and overall haemostatic potential (OHP). Fibrin structure was visualised using scanning electron microscopy (SEM). The permeability coefficient Ks decreased significantly after FVIII treatment. Ks correlated significantly with FVIII levels and dosage, and with ETP, OHP and levels of TAFI. SEM images revealed irregular, porous fibrin clots composed of thick and short fibers before FVIII treatment. The clots had recovered after FVIII replacement almost to levels in control samples, revealing compact fibrin with smaller intrinsic pores. To the best of our knowledge, this is the first description of fibrin porosity and structure before and after FVIII treatment of selected haemophilia patients. It seems that thrombin generation is the main determinant of fibrin structure in haemophilic plasma.
Keywords: Fibrin clot structure; scanning electron microscopy; FVIII; haemophilia A